AKIBAT HUKUM PUTUSAN PERNYATAAN PAILIT - Saryana S.H., M.Si (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2012)
Bankruptcy is all things related to the bankrupt event, i.e. borrowers' circumstances which are unable to pay its debts which have matured. With the declaration of bankruptcy, the bankrupt debtor was losing its rights in law to control and manage their wealth belonging to the bankruptcy estate. Bankrupt debtor's assets become jointly guarantee for all creditors. This means that if the debtor does not repay the debt default, the proceeds of the debtor's assets are distributed in proportion to (a pari passu) by the amount of accounts receivable of each creditor unless the creditor among the reasons that there are legitimate reasons to take precedence over creditors the other. The concurrent creditors are creditors who do not have a preferred position or precede other creditors. The preference creditors are creditors who have a preferred position or preceded other creditors. The classified as preference creditor are the privileged of credit holders, lien holders, mortgage holders, and holders of fiduciary.